Amperometrıc Tıtratıon Of Ions Sn (IV), Sb (III), W (VI) By Solutıon of Derıvatıves of Thıocarbasones In Non-Aqueous Medıa - Yakhshieva Zukhra, Kalonov Rustam, Bakakhonov Anvar (International Journal of Advanced Science and Technology, 2020)
The paper presents the experimentally obtained results, the conditions and the possibility of amperometric titration of Sn (IV), Sb (III), W (VI) with solutions of 4–4-methoxyphenylcarboxymethyldiethyldithio carbamate and phenyl carboxymethyl diphenylthiocarbazone in a wide range of its concentrations and optimization of titration conditions for various titration conditions main properties of buffer mixtures and background electrolytes.